Teaching and Learning Aids to Support the Deaf Students Studying Islamic Education. - Dzulkifli, Izuli (Pertanika Journal of Social Sciences & Humanities, 2021)
Islamic Education's formal teaching and learning for deaf students in schools are based on the Special Education Curriculum. In order to improve the achievement in the teaching and learning of deaf students, teachers should utilize teaching aids that are appropriate to the learning content and the students' ability. The objective of this study is to explore the use of teaching aids by teachers teaching Islamic Education subjects to deaf students at the primary school level in Selangor. This study utilized the qualitative approach in the form of case studies by using the interview technique and document analysis to obtain data. Seven teachers from schools offering the Special Education Integration Program (Program Pendidikan Khas Integrasi) and one teacher from the Special Education School (Sekolah Pendidikan Khas) were selected as study respondents. The study respondents were selected based on the purposive sampling technique and had at least five years of teaching experience in Islamic Education subjects to deaf students. The findings showed there were several main types of teaching aids used by the respondents. They were printed materials, the use of Information and Communication Technology and by-product materials. The study also discovered several challenges faced by the respondents when using the teaching aids such as lack of appropriate and limited materials as well as the information and communication technology software was less friendly to deaf students in the learning of Islamic Education. This study contributes in terms of the recommendations of the production of appropriate teaching aids in order to assist teachers in teaching and helping to improve students' achievement in Islamic Education learning.